Owning Russia : the struggle over factories, farms, and power - Barnes, Andrew Scott, 1969- (Cornell University Press, 2006)
"During and after the breakdown of the Soviet Union, a wide range of competitors fought to build new political and economic empires by wresting control over resources from the state and from each other. In the only book to examine the evolution of Russian property ownership in both industry and agriculture, Andrew Barnes uses interviews, archival research, and firsthand observation to document how a new generation of capitalists gained control over key pieces of the Russian economy by acquiring debt-ridden factories and farms once owned by the state. He argues that although the Russian government made policies that affected how actors battled one another, it could never rein in the most destructive aspects of the struggle for property." "Barnes shows that dividing the spoils of the Soviet economy involved far more than the experiment with voucher privatization or the scandalous behavior of a few Moscow-based "oligarchs." In Russia, the control of property yielded benefits beyond mere profits, and these high stakes fueled an intense, enduring, and profound conflict over real assets. This fierce competition empowered the Russian executive branch at the expense of the legislature, dramatically strengthened managers in relation to workers, created a broad array of business conglomerates, and fundamentally shaped regional politics, not only blurring the line between government and business but often erasing it."--Jacket